Foreign Languages and Trade - Jan Fidrmuc; Jarko Fidrmuc (Center for Economic Studies and ifo Institute (CESifo), 2014)
Cultural factors and especially common languages are well-known determinants of trade. By contrast, the knowledge of foreign languages was not explored in the literature so far. We combine traditional gravity models with data on fluency in the main languages used in EU and candidate countries. We show that widespread knowledge of languages is an important determinant for foreign trade, with English playing an especially important role. The robustness of our results is confirmed by a natural experiment of trade between Eastern and Western Europe.
Keywords: C23; F15; F40; Z10; 330; gravity model; foreign trade; economics of languages; natural experiment; median regression; quantile regression